2002
DOI: 10.1038/sj.mp.4001116
|View full text |Cite
|
Sign up to set email alerts
|

State-dependent alterations in mitochondrial complex I activity in platelets: a potential peripheral marker for schizophrenia

Abstract: Keywords: schizophrenia; mitochondrial complex I; human 24-, 51-and 75-kDa subunits of complex I; platelets; biological marker Schizophrenia, the most severe psychiatric disorder, is characterized by heterogeneity of clinical signs, often categorized into positive and negative symptoms. Among a wide array of competing biological mechanisms, altered cerebral energy metabolism and mitochondrial dysfunction have been suggested to play an important role in the pathophysiology of schizophrenia. In this study we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
81
5
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(106 citation statements)
references
References 32 publications
12
81
5
8
Order By: Relevance
“…In the ACC gray matter, the 13 kDa-B subunit of Complex 1 is decreased 1.944 fold in schizophrenia compared to controls. This is in corroboration with previous studies, which report lower activity of complex 1 in the temporal cortex, basal ganglia 29 and in platelets of patients with residual schizophrenia 35 as well as diminished mRNA levels in the dentate gyrus 34 and reduced level of protein in both the gray and white matter proteomes of the PFC in schizophrenia. 18 Dror et al further found complex 1 activity to be associated with psychotic symptomatology.…”
Section: Metabolismsupporting
confidence: 93%
See 1 more Smart Citation
“…In the ACC gray matter, the 13 kDa-B subunit of Complex 1 is decreased 1.944 fold in schizophrenia compared to controls. This is in corroboration with previous studies, which report lower activity of complex 1 in the temporal cortex, basal ganglia 29 and in platelets of patients with residual schizophrenia 35 as well as diminished mRNA levels in the dentate gyrus 34 and reduced level of protein in both the gray and white matter proteomes of the PFC in schizophrenia. 18 Dror et al further found complex 1 activity to be associated with psychotic symptomatology.…”
Section: Metabolismsupporting
confidence: 93%
“…18 Dror et al further found complex 1 activity to be associated with psychotic symptomatology. 35 In addition, the gene encoding the 13 kDa-B subunit, located on chromosome 7, has also previously been associated with schizophrenia. 36,37 The reduced abundance of enzymes involved in each stage of cellular respiration suggests depleted glucose metabolism leading to oxidative stress of the ACC in the pathology of schizophrenia.…”
Section: Metabolismmentioning
confidence: 99%
“…Several studies indicate that ND4 is essential for the assembly of complex I 29 and could be involved in the ion channel formation for H þ pumping within the enzyme 30 and the introduction of a histidine in position 446 of the ND4 subunit could affect NADH-ubiquinone oxidoreductase activity. Since complex I activity in schizophrenic patients has been related to psychotic symptomatology, 31 we suggest that the MTND4 12096T4A mutation could participate in this relationship. The fact that this mutation is not found in homoplasmy also reflects the importance of the change in the microenvironment of the protein.…”
Section: Discussionmentioning
confidence: 86%
“…These proteins belonged to the glycolytic pathway [110] , indicating that impaired glycolytic response could be a potential early stage of diagnostic biomarker for Sz. Mitochondrial complex Ⅰ, the first enzyme in the mitochondrial respiratory chain for the oxidation of glucose, was found to have increased activity in the platelets from people with Sz [108] and to have higher mRNA levels in blood from people with Sz [111,113] . It has also been reported that the activity of platelet mitochondrial complex Ⅰ is associated with positive symptoms and clinical disease course in people with Sz [108] .…”
Section: Metabolismmentioning
confidence: 99%